Mutu kulit glase dari kulit domba peranakan merino - Oetojo, Bambang; Lutfi, Muchtar; Widari, Widari; Basalamah, Hasan (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1990)
This research used four pieces of good quality merino descendent sheep skin and four pieces of good quality local sheep of glace leather produced from merino descendent sheep skin to that one from local sheep skin. Either merino descendent sheep skins or the local ones were processed into glase leather through the ordinary tanning method. Glace leather output from this research were visual investigated and physical tested.Â Statistical analysys points out that there is unsignify difference (P â¼ 0,05) the influence of the species either it is merino and the stretch of glaze leather. It is also unsignify difference (P â¼ 0,05) the influence of the species either it is merino descendent sheep skin or the local one to the quality of glaze leather.Pratical meaning of this research is that merino descendent sheep skin may be tanned into glaze leather having same quality to that one from local sheep skins.Â